Arktinen matka - kokeellinen näyttely - Miettinen, Satu Anneli; Jeminen, Jaana; Tikkanen, Heikki; Vuorikari, Tytti Marianne; Jylkäs, Titta Niina Joanna (2016)
Kokeellinen yhteisnäyttely: Satu Miettinen, Titta Jylkäs, Tytti Vuorikari, Heikki Tikkanen, Jaana Jeminen Poster interventions: June 13th -17th 2016 Stanford University Campus, Palo Alto and University of California, Berkeley Campus, CA, USA Workshop and Exhibition: March 17th -18th 2016, Parsons the New School for Design, NY, USA “My wings to fly” –textile installation and videoworkshop: April 8th-22nd 2016, Refection Gallery, Jutila Center, Hancock, MI Video installation: May 25th - 30th 2016, Emily Carr University of Art + Design, Vancouver, Canada